Prevalence of Comorbid Personality Disorder in Psychotic and Non-psychotic Disorders - Wang, Qiang; Zhang, Lei; Zhang, Jiechun; Ye, Zhihao; Li, Ping; Wang, Feng; Cao, Yili; Zhang, Shaojun; Zhou, Fang; Ai, Zisheng; Zhao, Nan (Frontiers in Psychiatry, 2021)
Introduction: The burden of personality disorders (PDs) in China is large and the focus on mental health services is increasing. However, there is a lack of sufficient evidence regarding the prevalence of comorbid PD in psychotic and non-psychotic disorders, and whether PDs have different distributions. We aimed to investigate the PD comorbidity distribution pattern between psychotic and non-psychotic disorders using a clinical population-based study. Materials and Methods: We conducted a cross-sectional study of 1,497 patients in Shanghai. PDs were assessed using the Personality Diagnostic Questionnaire Fourth Edition Plus (PDQ-4+) and patients were interviewed using the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV) Axis II (SCID-II). We compared the differences in PD comorbidities classified as per the DSM-IV, across the ten types of PDs, in 531 patients with psychosis and 966 patients with non-psychotic disorders. Results: More than one-third (37%) of patients with psychotic disorders met the criteria of at least one PD. Approximately half (46%) of patients with non-psychotic disorders met the criteria of at least one PD. Patients with non-psychotic disorders were more likely to meet the criteria of borderline (χ2=20.154, p<0.001) and obsessive-compulsive PD (χ2=21.164, p<0.001) diagnoses compared to those with psychotic disorders. In contrast, patients with psychotic disorders were more likely to meet the criteria of paranoid (χ2=11.144, p=0.001) and schizotypal PD (χ2=14.004, p<0.001) diagnoses than those with non-psychotic disorders. Discussion: PD comorbidity is common in patients with psychotic and non-psychotic disorders in Shanghai, implicating the development of specific strategies that could screen and assess PDs in psychiatric clinical practice.